Ultrasonic velocity and attenuation in carbon steel specimens - Buitrago, Brenda; Irausquín, Ignacio; Mendoza, Johnny (Rev. Téc. Fac. Ing. Univ. Zulia)
Materials testing and inspection by means of the ultrasonic nondestructive method, has become an useful and sensitive tool to determine its acoustic properties. By virtue of this, the purpose of the following study was to measure the longitudinal ultrasonic velocity and to estimate the ultrasonic attenuation for three carbon steel specimens. This ultrasonic characterization was done by means of the pulse-echo technique using transducers with a diameter of 0.375” (9.525 mm) and center frequencies of 1.5, 2.25, 5, 7.5 and 10 MHz, besides glycerin as coupling. Results showed an insignificant change in the frequency spectrum of each specimen and significant changes of its attenuation. Like wise differences in velocity and attenuation were found between the specimens, proportionally to its carbon concentration.